Education Transformation: Paradigm Shifts in Learning in the Age of Technology - Istiqomah, Nurul; Na'imah, Na'imah (FKIP - Universitas Riau, 2025)
The transformation of education in the era of digital technology presents both challenges and opportunities in improving the quality of learning. This research aims to analyze the community's response to the changing learning paradigm influenced by the integration of digital technology. The research method used is descriptive qualitative with a literature study approach. The results show that educational transformation does not only include the use of digital devices, but also a paradigm shift from teacher-centered learning to active, collaborative and flexible learning models that are learner-oriented. The community shows a positive response to the utilization of applications such as Quizizz, Canva, as well as Augmented Reality (AR) and Virtual Reality (VR) technologies, which are considered capable of creating an interactive, fun learning atmosphere and encouraging student creativity. This finding shows that conventional approaches are falling behind in meeting the demands of 21st century learning. Therefore, progressive education policies, improved teacher competencies, and equitable access to digital infrastructure at all levels and regions of education are needed.